Chemical Composition, Anti-inflammatory, Analgesic, Antipyretic, Myorelaxant, Antibacterial and Antifungal activity of Rabdosia rugosus Wall. (Syn. Plectranthus rugosus Wall.) - Ravendra Kumar, Prakash Singh; Anil Kumar Pant, Om Prakash; Kumar, Mahesh; Lech Szczepaniak, Valary A. Isidorov (Journal of Medicinal Herbs and Ethnomedicine, 2019)
For the present investigation Rabdosia rugosus Wall. Syn. Plectranthus rugosus Wall. was collected from Pancheshwar, Uttarakhand on the way to Badrinath. The GC and GC-MS analysis, revealed the presence of more than forty compounds out of which 35 compounds were identified amounting to 97.3% of the total oil. The essential oil of R. rugosus was rich in sesquiterpinoids ( 90%) and was poor in monoterpenoids (8.1%). α-bisabolol (41.9%) was the major constituent of the oil and the other identified major compounds were germacrene-D (9.7%), β-caryophyllene (7.6%), dehydroabietane (5.2%), ar-curcumene (5.0), trans-ferruginol (3.3%) α-cadinol (3.2%), τ-muurolol (2.3%), p-Cymene (3.2%) and γ-terpinene (2.0%). The essential oil of Rabdosia rugosus showed insignificant anti-inflammatory and analgesic activity but shows significant antipyretic, myorelaxant and antimicrobial activity.